Two year efficacy and safety of small versus large ABSORB bioresorbable vascular scaffolds of ≤18 mm device length: A subgroup analysis of the German-Austrian ABSORB RegIstRy (GABI-R). (April 2020) - Zaczkiewicz, Myron; Wein, Bastian; Graf, Matthias; Zimmermann, Oliver; Kastner, Johannes; Wöhrle, Jochen; Thomas, Riemer; Hamm, Christian; Torzewski, Jan; ,
Abstract: Aims: The ABSORB bioresorbable vascular scaffold raised safety concerns due to higher rates of scaffold thrombosis (ScT) and adequate scaffold diameter and length for scaffold technology. Smaller scaffold diameter (SScD, 2.5 mm) was an infrequently quoted predictor of major adverse cardiac events (MACE). Therefore, we evaluated the impact of SScD compared to large scaffold diameter (LScD, ≥3 mm) of ≤18 mm device length on 2 year outcome in the all-comer real life GABI-R cohort. Methods and Results: We compared patients with implanted LScD (1341 patients) vs. SScD (444 patients) of ≤18 mm device length. Patients with LScD more often presented with ST-elevation myocardial infarction (35.8% vs. 20.6%, p < 0.0001) and single-vessel disease (50.6% vs. 36.5% p < 0.0001). After a 24 months follow-up, there was no difference in regard of MACE (9.66% vs. 12.31%, p = 0.14) or definite/probable ST (2.47% vs. 2.82%, p = 0.71). Despite no difference in target lesion revascularisations (TLR) (5.81% vs. 7.71%, p = 0.18), there was a higher need for target vessel revascularisation (TVR) in the SScD-group (11.57% vs. 7.51%, p < 0.05). Conclusion: Compared to LScD, SScD of ≤18 mm device length demonstrated comparable safety in regard to MACE and ScT as well as efficacy in regard to TLR. Resorbable scaffold technology should not be restricted to large vessel diameters. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT02066623 .